Bolivia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Preliminary estimates show that pension costs will continue to grow for several years, and controlling and curbing pension costs will be a challenge for Bolivia. Market-friendly reforms could limit the scope for dollarization and its risks. A gradual shift toward a more flexible exchange rate regime will help Bolivia to face adverse shocks. This paper summarizes the main components of Bolivia's strategy to strengthen the financial and corporate sectors. The statistical data on economic indices of Bolivia are also presented in the paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet